A rapid method of analysis of corn grain fordairy cattle - G. Garcia; R. Malvetti; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1989)
Calibration equations for near infrared reflectance spectroscopy (NIRS) have been either purchased from the manufacturer or developed in the laboratory. Comparative analysis with standard laboratory procedures indicate that NIRS may be used for analyzing dairy feedstuffs, when proper calibration is made with local feedstuffs. NIRS is a new, rapid method of analyzing feedstuffs that reduces the time from several days to one minute or more after grinding and subsampling. The instrument needs to be calibrated from nutrient analyses made in the laboratory. Many calibrations may be purchased from the manufacturer of the instrument; however, we have found that many Kansas feedstuffs do not lend themselves well to purchased equations. Purchased equations that do appear to give acceptable results include those for alfalfa hay, mixed hay, grass hay, and corn silage. Sorghum silage equations are inadequate for the many cultivars in this state, and those for corn and milo were too expensive to purchase.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Corn grain; Near infrared reflectance spectroscopy (NIRS)